Energy and emissions balance of modal shift in freight transport: A case study from the Central European region - Bulková, Zdenka; Zitrický, Vladislav; Ľupták, Vladimír; Brabec, Jan; Pečman, Jan (Transportation research interdisciplinary perspectives, 2025)
•A comprehensive comparison of energy consumption and CO2 emissions between road and rail freight transport using real traffic flow data.•Modal shift analysis in the Czech Republic demonstrates alignment with EU decarbonization and energy efficiency targets.•Novel methodology for calculating specific energy consumption of electric locomotives in Austria, Germany, and the Czech Republic.•Data-driven modeling enables accurate emission assessment and supports sustainable freight transport planning.•Promoting freight transfer from road to rail contributes to achieving the EU Green Deal objectives. Freight transport is a major contributor to energy consumption and greenhouse gas emissions in the European Union. Despite European Union strategies promoting a modal shift from road to rail, road freight still dominates in Central Europe. This paper addresses the gap in comparative analyses of energy intensity and environmental impact between road and rail freight by proposing a detailed calculation methodology. The approach combines direct measurement of electric locomotive consumption in Austria, Germany, and the Czech Republic with operational data from road freight transport. Specific energy consumption, CO2 emissions, and transport performance are evaluated and compared using real transport flows in the Czech Republic. The results confirm that shifting 9.75 % of freight from road to rail can reduce energy consumption by 85.3 % and emissions by 75.7 %, equivalent to annual savings of 212 million kWh and 59,000 tonnes of CO2. Although the case study focuses on the Czech Republic, the proposed methodology is also applicable to other Central European countries with similar transport flows, energy mixes, and infrastructure. The results therefore provide a relevant framework for the broader region, which faces comparable challenges in the decarbonization of freight transport.